2021
DOI: 10.1088/1755-1315/937/3/032010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of design parameters on the agro-ecological qualities of tractor tires

Abstract: Experimental studies of the impact of agricultural mobile machinery movers on the soil are seasonal in nature and require complex experimental equipment. The complexity of the physical processes occurring in the elastic wheel-ground system requires the introduction of many assumptions and limitations that reduce the accuracy of the results, according to the design of simulation models performed in the software environment. The aim of the research was to study the influence of the design parameters of the tire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…2222440, 2299135, 2398147, 2739100, etc.). His operation is described in detail in the literature [2,3,9,10,11].…”
Section: Results Of the Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…2222440, 2299135, 2398147, 2739100, etc.). His operation is described in detail in the literature [2,3,9,10,11].…”
Section: Results Of the Researchmentioning
confidence: 99%
“…The data of the conducted operational tests, which were carried out on plowing, continuous cultivation and sowing, showed that the studied EDM with optimal parameters [9][10][11], located in the power transmission of the 1.4 drawbar category MPT at the sufficiently high level provides protection for all components links of the MTU from fluctuations of external and internal links, which has a positive effect on the dynamic processes that occur in all elements of the MTU [2-8]. So, for example, as a result of testing an plowing MTU in the field, it was found that the application of EDM into the power transmission of the 1.4 drawbar category mobile power tool helps to reduce the amplitude of the hook force fluctuations compared to the serial version to 15 ... 20%.…”
Section: Results Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main ways to increase the performance indicators of any tire-tractor unit (TTU) is its operation at high speeds and the use of agricultural machines with a large gripping width, which implies the use of mobile energy means with high traction characteristics when aggregating [2]. But at the same time, normal and tangential stresses in the contact imprint of the MEM propellers with a supporting base are constantly increasing, which leads to an increased negative impact on the soil, up to its destruction [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For any wheeled MEM, the achievement of high traction performance, smooth running, the level of compacting effect on the support base, as well as the characteristics of movement along a given trajectory will be determined by the elastic properties of the driving wheel tires [2,11].…”
Section: Introductionmentioning
confidence: 99%